Domain‐specific distribution of gap junctions defines cellular coupling to establish a vascular relay in the retina. Issue 16 (13th April 2019) - Ivanova, Elena; Kovacs‐Oller, Tamas; Sagdullaev, Botir T.
Abstract: In the retina, diverse functions of neuronal gap junctions (GJs) have been established. However, the distribution and function of vascular GJs are less clear. Here in the mouse retina whole mounts, we combined structural immunohistochemical analysis and a functional assessment of cellular coupling with a GJ‐permeable tracer Neurobiotin to determine distribution patterns of three major vascular connexins. We found that Cx43 was expressed in punctate fashion on astroglia, surrounding all types of blood vessels and in continuous string‐like structures along endothelial cell contacts in specialized regions of the vascular tree. Specifically, these Cx43‐positive strings originated at the finest capillaries and extended toward the feeding artery. As this structural arrangement promoted strong and exclusive coupling of pericytes and endothelial cells along the corresponding branch, we termed this region a "vascular relay." Cx40 expression was found predominantly along the endothelial cell contacts of the primary arteries and did not overlap with Cx43‐positive strings. At their occupied territories, Cx43 and Cx40 clustered with tight junctions and, to a lesser extent, with adhesion contacts, both key elements of the blood–retina barrier. Finally, Cx37 puncta were associated with the entire surface of both mural and endothelial cells across all regions of the vascular tree. This combinatorial analysis of vascular connexins and identification of the vascular relay region will serve as a structural foundation for future studies of neurovascular signaling in health and disease. Abstract : In the mouse retina vasculature, we have determined connexins' distribution and cellular coupling. Cx43 strings connected capillaries with the feeding artery and promoted coupling. We termed this region a "vascular relay." Cx40 expression was in primary arteries. Cx37 puncta were on majority of vascular cells.